Political positioning strategy of the Partai Demokrasi Indonesia Perjuangan (PDIP) in the case of the Free Nutritious Meal Program (MBG) - Dimas Subekti (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2026)
The Free Nutritious Meal Program (MBG) championed by the Prabowo Subianto administration has become a strategic policy to improve the quality of human resources through nutritional fulfillment, but it has faced various criticisms, including from the PDIP. Although the PDIP criticized aspects of the budget, implementation, and potential politicization, the party still approved the program during the legislative process. Therefore, this research aims to analyze the Political Positioning Strategy of the Partai Demokrasi Indonesia Perjuangan (PDIP) in the Case of the Free Nutritious Meal Program (MBG). This research uses a qualitative method with a case study approach. The data collection technique in this research employs literature study. The findings of this study explain that the political positioning strategy of the Partai Demokrasi Indonesia Perjuangan (PDIP) in the case of the Free Nutritious Meal Program (MBG) demonstrates an adaptive approach. The combination of these three strategies shows that PDIP not only seeks to attract electoral support but also builds political legitimacy through a balance between responsiveness to the public, institutional performance, and value differentiation. In the context of a competitive multiparty system, such positioning becomes a strategic advantage because it allows the Party to remain relevant as a political institution that is not merely populist, but also rational and possesses a distinctive political character.